Gelatine modified monetite as a bone substitute material: An in vitro assessment of bone biocompatibility. (1st March 2016) - Kruppke, Benjamin; Farack, Jana; Wagner, Alena-Svenja; Beckmann, Sarah; Heinemann, Christiane; Glenske, Kristina; Rößler, Sina; Wiesmann, Hans-Peter; Wenisch, Sabine; Hanke, Thomas
Graphical abstract: Abstract: Calcium phosphate phases are increasingly used for bone tissue substitution, and the load bearing properties of these inherently brittle biomaterials are increased by inclusion of organic components. Monetite prepared using mineralization of gelatine pre-structured through phosphate leads to a significantly increased biaxial strength and indirect tensile strength compared to gelatine-free monetite. Besides the mechanical properties, degradation in physiological solutions and osteoblast and osteoclast cell response were investigated. Human bone marrow stromal cells (hBMSCs) showed considerably higher proliferation rates on the gelatine modified monetite than on polystyrene reference material in calcium-free as well as standard cell culture medium (α-MEM). Osteogenic differentiation on the material was comparable to polystyrene in both medium types. Osteoclast-like cells derived from monocytes were able to actively resorb the biomaterial. Osteoblastic differentiation and perhaps even more important the cellular resorption of the biomaterial indicate that it can be actively involved in the bone remodeling process. Thus the behavior of osteoblasts and osteoclasts as well as the adequate degradation and mechanical properties are strong indicators for bone biocompatibility, although in vivo studies are still required to prove this. Statement of Significance: New and unique? A low temperature precipitationprocessforcalcium anhydrous hydrogen phosphateallows for the first time to produce monolithic compact composites of monetite and gelatine. The composite is degradable and resorbable. To prove that, the question arises: what is bone biocompatibility? The reaction of both mayor cell types of bone represents this biocompatibility. Therefore, human bone marrow stromal cells were seeded revealing the materials pro-osteogenic properties. Monocyte cultivation, becoming recently focus of interest, revealed the capability of the biomaterial to be actively resorbed by derived osteoclast-like cells. Not new but necessary ismechanical characterization, which is often only investigated as uniaxial property. Here, a biaxial method is applied, to characterize the materials properties closer to its application loads.